Max Aub / Buñuel. Todas las conversaciones - H. Wood, Guy (Buñueliana, 2023)
Reseña de: Xifra, J. (ed.), Max Aub / Buñuel. Todas las conversaciones, Zaragoza, Prensas de la Universidad de Zaragoza, 2020, 1049 pp.